Analisis Perencanaan dalam Pemanfaatan Rest Area pada Jalan Tol Kawasan Probolinggo - Setiamandani, Emei Dwinanarhati; Firdausi, Firman; Dewi, Dewa Ayu Putu Shandra; Setiawan, Muhammad Nur Romi Amin (Indonesian Social Science Review, 2024)
Development planning on a global and national scale has a very clear direction. This is stated in the SDG's which were updated after the MDG's program. In SDG's planning, it is very important to have an element of sustainability in terms of products, energy, natural resources and human resources. One of the infrastructure developments in Indonesia, one of which is toll roads. The construction of toll roads must also annul the objectives of the direction of development in Indonesia and globally. One that is built in the construction of highways is a rest area. Utilization of rest areas on toll roads has a socio-environmental impact on the surrounding area. The Probolinggo highway is a new road so studies are needed for future development. This study uses a qualitative method based on description. Through primary and secondary data analysis, it was found that the construction of a rest area in the Probolinggo area annulled the important points of the SDGs by using sustainable development and involving all development actors as rest area partners. Perencanaan pembangunan di dunia dan skala nasional sudah sangat jelas arahnya. Hal ini tertuang dalam SDG’s yang diperbarui setelah program MDG’s. Pada perencanaan SDG’s penting sekali adanya unsur keberlanjutan baik dari segi produk, energi, sumber daya alam dan sumber daya manusia. Salah satu pembangunan infrastruktur di Indonesia salah satunya adalah jalan tol. Pembangunan jalan tol juga harus menganulir tujuan dari arah pembangunan di Indonesia maupun global. Salah satu yang dibangun dalam pembangunan jalan tol adalah rest area. Pemanfaatan rest area di jalan tol memiliki dampak sosial-lingkungan pada wilayah yang ada di sekitarnya. Jalan tol probolinggo merupakan jalan tol yang masih baru sehingga diperlukan kajian-kajian untuk pengembangan pembangunan dalam jangka waktu di masa depan. Penelitian ini menggunakan metode kualitatif yang berbasis pada deskripsi. Melalui analisa data primer dan sekunder ditemukan bahwa pembangunan rest area di kawasan probolinggo menganulir poin penting dari SDG’s dengan menggunakan sustainable development dan melibatkan semua aktor pembangunan sebagai mitra rest area.